2009
DOI: 10.3171/2009.6.spine08710
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transplantation of human umbilical cord blood–derived multipotent stem cells in a canine model of spinal cord injury

Abstract: Object The authors describe a method for percutaneous transplantation of human umbilical cord blood (hUCB)–derived multipotent stem cells (MSCs) under fluoroscopic guidance. The investigators then tested whether percutaneous transplantation of hUCB-derived MSCs improved neurological functional recovery after acute spinal cord injury (SCI). Methods The authors induced SCI in 10 dogs by percutaneous balloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…However, we previously reported that these hUCBMSCs survived in dogs with SCI for 4 weeks [9]. Further, Saporta et al [5] have previously reported that intravenously infused hUCB cells survived in the injured spinal cord until 3 weeks after the infusion and this had improved motor functions in a rat after SCI.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…However, we previously reported that these hUCBMSCs survived in dogs with SCI for 4 weeks [9]. Further, Saporta et al [5] have previously reported that intravenously infused hUCB cells survived in the injured spinal cord until 3 weeks after the infusion and this had improved motor functions in a rat after SCI.…”
Section: Discussionmentioning
confidence: 95%
“…Characterization and differentiation of isolated hUCB-MSCs were performed in another study using the same cell source and isolation technique [7,10,16]. It was also suggested that these hUCB-MSCs are capable of differentiating into neural cells in vitro [17] and in vivo [9,16]. The hUCB-MSCs were provided for pure research purposes by the Seoul Cord Bank (Histostem Co., Ltd., Seoul, Korea).…”
Section: Hucb-msc Harvest and Preparationmentioning
confidence: 99%
See 3 more Smart Citations